The effect of alpha-lactalbumin consumption on sleep quality and quantity in female rugby union athletes: a field-based study - Gratwicke, M.; Miles, K. H.; Clark, B.; Pumpa, K. L. (Biology of Sport, 2023)
This double-blind randomised placebo-controlled trial aimed to investigate the effects of a-lactalbumin consumption on sleep quality and quantity in female rugby union athletes during a competition season. Eighteen semi-professional female rugby union players (age 23.8 ± 5.2 y; mean ± SD) wore wrist actigraphy watches for four seven-day blocks corresponding to the pre-season, a home game, a bye week (i.e. no competition game scheduled) and an away game. Participants consumed either an alpha-lactalbumin (alpha-LAC), or placebo drink (PLA) every night two hours before bed for the duration of the season. Generalised linear mixed models were used to investigate the effects of the nutritional intervention on sleep variables (total sleep time, sleep efficiency (SE), sleep onset latency (SOL) and wake after sleep onset) over the duration of the season. There was a significant condition by period interaction effect on SOL (p = 0.01). While similar at baseline (23.3 ± 16.3 and 23.2 ± 18.9 min a-LAC and placebo respectively) and for the home game (22.4 ± 17.6 and 19.3 ± 14.9 min a-LAC and placebo respectively), SOL was reduced in the alpha-LAC group for the bye (11.6± 13.4 min) and away game (17.0 ± 11.5 min; p = 0.045). In comparison, SOL remained unchanged in the PLA group (bye 21.2 ± 17.3 and away 22.5 ± 18.5 min). Pre-sleep a-lactalbumin consumption improved SOL in a semi- professional female team-sport cohort. Thus, alpha-lactalbumin could be utilised by athletes to support sleep during a competitive season.